2009
DOI: 10.1021/ie801165u
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and SO2 Sorption/Desorption Behavior of an Ionic Liquid Supported on Porous Silica Particles

Abstract: The ionic liquid 1,1,3,3-tetramethylguanidinium lactate (TMGL) was supported onto porous silica particles via a facile impregnation-vaporization method. The TMGL-supported particles gave high porosity and large specific surface area. The SO 2 sorption/desorption properties of the silica-supported TMGL (TMGL-SiO 2 ) were evaluated, and high SO 2 sorption capacity and rate were achieved. Its capacity reached 0.6 g SO 2 /g TMGL in 15-30 min with pure SO 2 gas and 0.15 g SO 2 /g TMGL in 17 h with a N 2 /SO 2 mixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
109
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(116 citation statements)
references
References 21 publications
6
109
0
1
Order By: Relevance
“…TMGL/SiO2 with different immobilization ratio was prepared through the impregnation-vaporization process [10] , and the TMGL/SiO2 ratio x/1 was expressed as TMGL/SiO2-x/1, equal to the TMGL/SiO2 feed ratio x/1. TMGL/SiO2-x/1 and TMGL were characterized by Thermal Gravimetric Analyzer (TGA).…”
Section: B Preparation and Characterization Of Tmgl/sio2mentioning
confidence: 99%
See 1 more Smart Citation
“…TMGL/SiO2 with different immobilization ratio was prepared through the impregnation-vaporization process [10] , and the TMGL/SiO2 ratio x/1 was expressed as TMGL/SiO2-x/1, equal to the TMGL/SiO2 feed ratio x/1. TMGL/SiO2-x/1 and TMGL were characterized by Thermal Gravimetric Analyzer (TGA).…”
Section: B Preparation and Characterization Of Tmgl/sio2mentioning
confidence: 99%
“…Unfortunately, their internal pore structures would be collapsed or mostly lost after many cycles of SO2 sorption. Subsequently, Li et al [10] immobilized TMGL to porous silica (SiO2) particles, which provided large gas-solid interface. They reported that it is an effective way to improve the absorption rate and capacity (1.9 mol SO2/mol TMGL with pure SO2) of TMGL.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the conveying of viscose IL for cyclic operation between absorption and regeneration may present another practical problem. In order to solve these problems, Li and Zhu and their coworkers proposed immobilization of ILs on solid materials by co-polymerization [27] and impregnation-vaporization methods [28]. They found that simply impregnating TMGL on porous silica particles gives a material maintaining the porous structure, large surface area and good mechanical properties of silica while taking the advantages of high SO 2 capacity of IL [28].…”
Section: Introductionmentioning
confidence: 99%
“…In order to solve these problems, Li and Zhu and their coworkers proposed immobilization of ILs on solid materials by co-polymerization [27] and impregnation-vaporization methods [28]. They found that simply impregnating TMGL on porous silica particles gives a material maintaining the porous structure, large surface area and good mechanical properties of silica while taking the advantages of high SO 2 capacity of IL [28]. Thereafter, various supported IL materials have been developed [29].…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] Uma grande parte desse interesse deriva, sem dúvida, do enorme desafio ambiental representado pelas concentrações crescentes de SO 2 na atmosfera, em grande parte decorrentes da queima de combustíveis fósseis. As estimativas da última década colocam a emissão de SO 2 na atmosfera na escala de 300 milhões de toneladas/ano no mundo.…”
Section: Introductionunclassified